На ринге ствол не нужен: [повести] / Николай Леонов, Алексей Макеев - Леонов Николай Иванович (Черная кошка, 2008)
Экземпляры: ф.15 (2011) / Инвентарный номер: 53708 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Л 47 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44^VLBC/RL